CLINICAL SIGNIFICANCE OF DRUGINDUCED INTERVALS QT AND QTC PROLONGATION - N. V. Furman; S. S. Shmatova (Столичная издательская компания, 2015)
Interval QT prolongation is a predictor of the life-threatening cardiac arrhythmias - polymorphic ventricular tachycardia (torsade de pointes). Long QT syndrome may be congenital or acquired. It is known that a wide range of both antiarrhythmic and non-cardiac medications might lead to QT interval prolongation. List of drugs that cause QT prolongation is constantly growing and being updated. The review contains current data on the clinical significance of the control of QT interval duration within drug therapy. Clinical conditions associated with an increased risk of QT interval prolongation are described. Drugs that can induce QT prolongation are also discussed.